Type 2 biliary perforation successfully managed with early insertion of self-expandable metal stent - Kurt, İdris (The European Research Journal, 2024)
Perforations after endoscopic retrograde colangiopancreatography (ERCP) are divided into four types. Type 1 refers to the duodenum, type 2 the periampullary region, type 3 the bile duct itself, and type 4 the observation of retroperitoneal free air on cross-sectional imaging. The treatment of type 2 biliary perforations remains debatable. We present a patient who was successfully treated with a self-expandable metal stent (SEMS) without the need for surgery or any complications.